Pengaruh Kompensasi, Kompetensi, dan Kepuasan Kerja terhadap Komitmen Organisasional (studi pada PT. Pos Indonesia cabang Erlangga Semarang) - Salsabilla Rachma Kanti Laras; Tristiana Rijanti (Universitas Sains dan Teknologi Komputer, 2024)
This study was conducted to analyse effect of compensation, competence, and job satisfaction on the organizational commitment of PT. Pos Indonesia Erlangga Branch Semarang and the sample used is 102 employees. This study uses primary data and data collection methods using questionnaire. The results of data processing are in the form of respondent descriptions, variable descriptions, validity test results, reliability test results, F test results, coefficient of determination test results (R2), and hypothesis test results. The results show that compensation variable has a positive and significant effect on organizational commitment, competence variable has a positive and significant effect on organizational commitment, and job satisfaction has a positive and significant effect on organizational commitment